Nilai Indeks Glikemik dan Indeks Transit Usus Tepung Porang (Amorphophallus muelleri Blume.) pada Mencit Putih - Laksmitawati, Dian Ratih; Prilasari, Sharon Alia; Marwati, Umi (Indonesian Research Gateway, 2017)
To prevent hyperglycemia, people need alternative source of carbohydrate with low glycemic index. Porang bulbs from Amorphophallus muelleri Blume plant is rich on glucomannan, that could prevent elevation of blood glucose level. The aim ofthis study is to determine aglycemic index and intestinal transit index of porang bulbs flour. Glycemic index determined by glucose tolerance test method and intestinal transit index determined by measuring the intestinal transit distance of mice administered 1,5 kg BW intragastically the porang suspense. Forty-five minute later mice was given carbo absorben as a marker. At 15 minute later mice was sacrificed by cervical dislocation and the distance of charcoal marker was measure from pillory. The results shows that porang has glycemic index 85 compare with glucose 100 and treatment with porang flour caused the intestinal motility was faster (intestinal transit index -0,42) rather than wheat four (0,32). Its mean that, porang flour shorten the retention time of chymus in intestinum s0 it will inhibit the absorbtion of'glucose. To prevent hyperglycemia, people need alternative source of carbohydrate with low glycemic index. Porang bulbs from Amorphophallus muelleri Blume plant is rich on glucomannan, that could prevent elevation of blood glucose level. The aim ofthis study is to determine aglycemic index and intestinal transit index of porang bulbs flour. Glycemic index determined by glucose tolerance test method and intestinal transit index determined by measuring the intestinal transit distance of mice administered 1,5 kg BW intragastically the porang suspense. Forty-five minute later mice was given carbo absorben as a marker. At 15 minute later mice was sacrificed by cervical dislocation and the distance of charcoal marker was measure from pillory. The results shows that porang has glycemic index 85 compare with glucose 100 and treatment with porang flour caused the intestinal motility was faster (intestinal transit index -0,42) rather than wheat four (0,32). Its mean that, porang flour shorten the retention time of chymus in intestinum s0 it will inhibit the absorbtion of'glucose.